Influence of reinforcement stiffness and compaction on the performance of four geosynthetic-reinforced soil walls. Issue 1 (1st February 2009) - Walters, D. L.; Allen, T. M.; Nernheim, A.; Saunders, D. D.; Bathurst, R. J.; Burgess, P.
Abstract : The paper describes measurements taken from a series of four full-scale modular block walls that were constructed with reinforcement layers having different stiffness. The walls were 3.6 m high and were reinforced with two different polypropylene geogrid reinforcement materials, a polyester geogrid and a welded wire mesh. Each wall was constructed with the same modular block facing and reinforcement spacing of 0.6 m. The influence of compaction effort on wall displacements and horizontal toe load measurements at the end of construction was detectable in this investigation. These values were adjusted to account for the influence of different compaction methods on end-of-construction wall response. However, during subsequent surcharging the effects of initial compaction effort were erased. Reinforcement loads are computed from strain readings and results of in-isolation constant-load (creep) tests. Computed maximum reinforcement loads are compared with values predicted using the current AASHTO Simplified Method and the K-stiffness Method. The predicted magnitude and distribution of reinforcement loads are shown to be more accurate using the K-stiffness Method for polymeric reinforcement materials. For the relatively stiff welded wire mesh product, the measured reinforcement loads fell between values predicted using both methods.